Potential insecticide of the ethanolic extract of Anadenanthera macrocarpa (BENTH.) in lepidopteran-pests - Lopes, Glauciany Soares; Silva, Luciana Barboza; Carneiro, Eliane; Silva Filho, Manoel Lopes da; Nery de Souza, Joao Sammy; Almeida, Fernandes Antonio; Pavan, Bruno Ettore [UNESP] (Univ Federal Mato Grosso, 2019)
The leafless worm complex - Spodoptera cosmioides, Spodoptera frugiperda and Helicoverpa armigera - are responsible for a considerable reduction in grain production. The application of botanical extracts is a viable and efficient alternative of control, besides being less harmful to the environment and human health. The objective was to evaluate the insecticidal potential of the raw extract of leaves and bark of Anadenanthera macrocarpa, on S. frugiperda, S. cosmioides, H. armigera. The insects were kept on artificial diet under controlled conditions. The toxic action of the extracts was evaluated by topical application. First the lethal concentration was estimated and then the biological parameters of the three lepidopteran species were determined. The extracts of leaves and bark of A. macrocarpa were efficient in the control of H. armigera, S. frugiperda and S.a cosmioides, reducing survival in 75, 60 and 50%, respectively, as well as changes in biological parameters such as larval period increase, weight reduction of larvae and pupae. The chemical compounds present in the leaves and bark extracts of A. macrocarpa, besides causing direct mortality of the studied insects, alter the biological cycle of S. frugiperda, S. cosmoides and H. armigera.
Keywords: Angico-black; Spodoptera cosmioides; Spodoptera frugiperda; Helicoverpa armigera; bioinsecticides